Green Synthesis of 3-(2-(4-(6-Fluorobenzo[d]isoxazol-3-yl)piperidin-yl) ethyl-6,7,8,9-tetrahydro-9-hydroxy-2-methylpyridol[1,2-a]pyrimidin-4-one - Vivekananda Reddy, D.; Sreelatha, P.; Dubey, P.K.; Rama Devi, B. (Asian Journal of Chemistry, 2014)
Paliperidone has been synthesized in high yields by condensation of 3-(2-chloroethyl)-9-hydroxy-2-methyl-6,7,8,9-tetrahy-dropyridol[1,2a]pyrimidin-4-one (1) and (2,4-difluoro-phenyl)-piperidin-4-yl-methanone oxime (2) using K2CO3 as a base, refluxing in acetonitrile for 16 h. The novel intermediate (3) underwent internal cyclization in PEG-600 as solvent yielded paliperidone (4). Paliperidone (4) from novel intermediate (3) has also been prepared under microwave condition using PEG-600 and also in presence of a base KOH in toluene at 70 °C for 3 h in higher yields.